Experimental Evaluation of the Physical and Sorption Properties of Gmelina Arborea Timber for Development of Wood-based Materials - Yusuf Yau; Amana Ocholi; Jibrin Muhammad Kaura; Adamu Lawan; Tasiu Ashiru Sulaiman (Covenant Journal of Engineering Technology)
The physical and sorption properties of wood are critical factors influencing its performance in various applications. These properties affect the strength and durability of wood products. Understanding these properties is essential for developing wood-based materials. This study focuses on the experimental investigation of Gmelina arborea timber to evaluate its sorption properties. The methodology involved a series of tests following ASTM, ISO, and BS standards to measure density, shrinkage and other various sorption properties. Key results showed a mean green moisture content of 141.28%, a basic density of 505.03 kg/m³, a dry density of 540.28 kg/m³, and a density at 12% moisture content of 555.17 kg/m³. The timber exhibits a volumetric shrinkage and swelling of 8.71% and 8.26%, tangential shrinkage and swelling of 5.19 and 4.96%, radial shrinkage and swelling of 3.72% and 2.82%, and longitudinal shrinkage and swelling of 1.19% and 0.48% respectively. The ratio of tangential to radial shrinkage was computed as 1.4, which indicates reliable dimensional stability of the timber. Gmelina arborea absorbs 94.7% water over a soaking period of 1272 hours and loses 83.18% moisture during drying to reach an equilibrium moisture content of approximately 12%. Therefore, Gmelina arborea shows good potential for use in the development of Engineered Wood Products such as Cross-laminated timber.